O conceito de revelação na Teologia Latino-Americana : uma abordagem a partir de João Batista Libanio - Osto, Leonardo Lucian Dall (2016)
This master research has as a goal to analyse the concept of revelation on the Latin- Americam theology, from the approach of João Batista Libanio theologian. It will verify how Libanio systematized the notion of revelation in the Teology of the release and which implications of this systematization for the Christian praxis and for the theology itself. For that, it approaches in the first chapter, the notion of revelation in the conciliar magisterium since the Council of Trent to the Council of Vatican II, reaching the corresponding translation of this concept in Latin-American Theology, specially through the approach done by Libanio. The second chapter tries to understand how Libanio creates the concept of revelation within the logical of historical liberation and which categories the author uses to see the divine action in the human history. The third chapter, according to Libanio’s theology, thematizes the revelation in the view of the option for the poor people,from the disclosure of the poverty as consequence of the sin and from the Basics Ecclesial Communities.) CEBs. Finally, in the last chapter, tries to show the God’s image that emerge from one view of revelation from the context of preferential option for the poor people and by its release and as Libanio, starting from God’s idea who reveals himself in the release of the poor people, he tries to elaborate one new Fundamental Theology.